How to Improve Student Understanding in Learning Science by Regulating Strategy in Language Education? Definition, Factors for Enhancing Students Comprehension, and Computational Bibliometric Review Analysis - Suherman, Irman; Fauziah, Siti Pupu; Roestamy, Martin; Bilad, Muhammad Roil; Abduh, Amirullah; Nandiyanto, Asep Bayu Dani (International Journal of Language Education, 2023)
The purpose of this study is to explain language education development research for improving student comprehension in learning science. This study also reviews the definition of these strategies, identifies factors that contribute to improving students' comprehension, and conducts a computational bibliometric review analysis to determine the efficacy of these approaches using Google Scholar with keywords "Language" and "Learning Science" from 2019 to 2023. There are also explanations for formal and informal learning, as well as educational levels for researching techniques and developing curriculum. The use of technology in media and laboratories is also a significant factor in increasing students' literacy and language impact. Language and student characteristics, motivation, teacher-student relationships, therapy, and psychological conditions are all inextricably linked. We also included information about language barriers for students with special needs, as well as new technologies that improve language learning, in which these can be factors in increasing student’s understanding of learning science. The bibliometric analysis results show that the trend of language research in learning science is decreasing year after year. This is due to the possibility that the focus of educational research has shifted to other areas, such as educational technology, science learning, or educational policy. The co-occurrence analysis results show several keywords that are frequently researched and should be paid attention to, including "language model," "natural language processing," "deep learning," "student," and "language learning." These keywords denote important parameters that can improve the learning experience because they enable personalized, interactive, adaptive educational interventions, particularly in language learning contexts, by adapting content and feedback to each student's needs and preferences. This paper will be useful to educators in better understanding the current state of affairs concerning the importance of language in engineering teaching and learning.